What do we need from intermediaries for technology transfer to China? A European firm perspective - Jason Li-Ying (Prometheus, 2012)
Cross-national technology transfer has been one of the most important vehicles by which firms in developed countries exploit the value of their technological innovations, and firms in developing countries gain access to technological and organizational knowledge from developed economies. To facilitate technology transfer between technology providers and recipients and to compensate for the weakness in the system of innovation, the role of technology intermediaries as bridging organizations has been widely recognized and discussed. This study deepens our understanding of the role of intermediaries by, first, reconciling the role and functions of technology intermediaries in the literature to a competence level based on a resource-based view in a specific context of technology transfer between Europe and China; and second, investigating whether certain competences of intermediaries are of more importance than others for European technology holders in relation to three different types of intermediaries – governmental agencies, private commercial agencies and web-based marketplaces.